Transition Counseling to Improve Career Adaptability of Vocational High School Students - Muhyidin1, Nurlathif (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
Currently, the ability to adapt to the world of work or career for Vocational High School (SMK) graduates is an issue in guidance and counseling services. Individuals who are able to adapt are characterized by the ability to pay attention to the future of their career, have a sense of responsibility, have curiosity and have confidence in accordance with the individual's interests. This research aims to produce a transition counseling model to increase vocational school students' career adaptability. The research uses a mixed method design sequence model with research and development methods with three stages, namely descriptive using the Career Adapt-Abilities Scale (CAAS) measuring tool, empirical testing using non-equivalent group design, and evaluative by evaluating the trial process transition counseling model which includes outcome evaluation and process evaluation